La motricidad fina en el proceso de preescritura en los niños del Subnivel Inicial II de 3 a 4 años - Cervantes Montaluisa, Johanna Estefanía (2020)
The present investigation work has been developed with the topic of fine motricity because of this is one of the most important elements of Education Beginners Teachers have to boost previous to the process of prewriting in each one of children. The age in which we work is Sublevel Initial of 3 or 4 years old in Britanico Los Andes School, in which previous it was done a diagnostic which I found some problem about muscular tonicity, digital precision, digital pin, manual hand eye, concentration and atention, special elements in Initial Educative Process, for which it was investigated about the topic before called and after it was designed a ludic work with didactic activities and innovator material wich strengthened in a good way the process of prewriting taking in count the needs and the context in which the children interact. The metodology used is the paradigm cuali quantify because it was applied evaluation instruments that served to measure quantify dates, they were used observation fichas and surveys that where applied to children, so it was used Investigation no experimental, it carried deliverated the variables. In wich to the resaults of Investigation they were positives because of the propose, it was had the significative have that children have in wich to the called aspects said it got better the significative way the weaknesses that children show about the named aspects before.